Anemia Affects One in Four Indian Men and Has Not Decreased in the Last Decade: Trends, Geographic Variability and Predictors from Nationally Representative Data, 2005 to 2016. (29th May 2020) - Pant, Anjali; Scott, Samuel; Nguyen, Phuong; Yadav, Kapil; Menon, Purnima
Abstract: Objectives: Men have largely been ignored in anemia-focused research and policies. We sought to examine trends, geographic variability, and predictors of anemia in Indian men between 2005 and 2016. Methods: We used data for men aged 15–54 years (n = 172, 717) from the 2005–2006 and 2015–2016 rounds of India's National Family Health Survey. To examine national and subnational anemia trends and variability, we computed survey-weighted prevalence at each timepoint for the full sample and by state. To examine factors associated with anemia, we used a multivariate logistic regression model adjusted for cluster sampling design, state fixed effects and survey year. Factors examined included age, marital status, education, residence type, employment type, wealth, diet, household characteristics, religion and caste. Results: Anemia among Indian men remained unchanged (23%) between 2006 and 2016 at the national level but trends varied by state (−6 to + 13 percentage points). In 2016, anemia was highest in adolescents 15–19 years (29%) and adults 50–54 years (30%). Higher likelihood of anemia was predicted by residence in rural areas (adjusted odds ratio (AOR) 1.24, 95% CI 1.18–1.30), employment in more labor intensive activities (AOR 1.12, 95% CI 1.07–1.18), being in the lowest wealth quintile (AOR 1.36, 95% CI 1.26–1.46), lack of improved sanitation facilities (AOR 1.11, 95% CI 1.06–1.16), Hindu religion (AOR 1.14, 95% CI 1.08–1.20) and being from a disadvantaged caste (AOR 1.07, 95% CI 1.01–1.12). Completing higher education (AOR 0.62, 95% CI 0.58–0.67) and consumption of animal source food at least once per week (AOR 0.98, 95% CI 0.96–0.99) predicted lower anemia prevalence. Conclusions: Anemia among men remains a moderate public health issue in India, thus men should be considered in anemia prevention policies. Improvements in diets, wealth, sanitation and education through family-targeted public programs may reduce anemia among men. Funding Sources: Bill and Melinda Gates Foundation.